A Faster Active Package to Cell Balancing of Battery Management System Using Isolated CUK Converter with Switch Matrix - Alperen Uğurluoğlu; Ahmet Karaarslan (Gazi Üniversitesi Fen Bilimleri Dergisi)
This paper proposes a faster active package to cell (P2C) balancing battery management system (BMS) by using a proportion-integration (PI) controlled isolated CUK converter (ICC) with a cell-selective switch matrix (SWM). The high power capability of the ICC and a SWM that has the ability to select each cell individually or multiple cells in series increase balance speed. In addition, the low cost analysis and small size comparisons of the proposed study are presented. BMS is applied to battery packs to monitor the voltage, current, temperature, and state of charge (SoC) values of each cell and provide the battery pack with the ability to operate in a safe zone. One of the battery problems is that each battery cell in the pack does not contribute energy equally to the entire pack. Li-ion batteries that are used in this paper also suffer from this problem due to their higher energy density than other batteries. Therefore, a balancing operation is needed for the voltage and SoC of each cell. According to the average of battery cells, the entire pack charges the selected lower cells by converting the energy through ICC and switching the lower energized cells. Due to the isolation, the energy can be transferred from pack to cell. The proposed study is simulated in MATLAB Simulink and then implemented experimentally. The experimental studies produce a balancing speed of 9.64 mV/min with 81.98% efficiency. Finally, the result of the proposed study is compared with the other P2C methods in the literature. The comparison also showed that the proposed study is a cost effective solution.